Gastrointestinal perforation in extremely low birth weight infants: A single center retrospective study in China - Wei Feng; Hong Zhang; Huan Yan; Zheng-Bing Yang; Jin-Liang Zhao; Li-Bing Zhang (Elsevier, 2024)
Background: Gastrointestinal perforation in extremely low birth weight infants, characterized by its rapid onset, multiple complications, and critical condition, poses a significant risk of infant mortality. The aim of this study was to investigate the clinical characteristics of pneumoperitoneum in extremely low birth weight infants (ELBWI) and explore the risk factors associated with gastrointestinal perforation in very low birth weight preterm infants. Additionally, we shared our surgical experiences in managing gastrointestinal perforation among extremely low birth weight infants. Methods: The Department of Neonatology at Chengdu Women and Children's Central Hospital conducted a retrospective study on gastrointestinal perforation in extremely low birth weight infants (birth weight <1000 g) who were admitted between 2014 and 2021. After baseline analysis and comparing it with the control group, we identified the risk factors associated with gastrointestinal perforation in ELBWI by multiple logistic regression analysis. The Kaplan-Meier analysis was performed to assess the adverse effect of gastrointestinal perforation for survival in ELBW infants. Cox multivariate regression analysis was used to evaluate hazard level of different variables for ELBW infants survival. Results: Hemodynamically significant patent ductus arteriosus (hsPDA)(p = 0.043, OR = 2.779) and sepsis (p = 0.014, OR = 2.265) were significant risk factors for gastrointestinal perforation in extremely low birth weight infants. The Cox proportional hazard model revealed that intraventricular hemorrhage (HR = 2.854, p＜0.001) Sepsis (HR = 1.645, p = 0.015) and gastrointestinal perforation (HR = 1.876, p = 0.008) had detrimental effects on the survival of extremely low birth weight infants; conversely, ibuprofen (HR = 0.304, p＜0.001) and blood transfusion (HR = 0.372, p＜0.001) are beneficial factors for their survival. The preoperative indicators of infection in infants with spontaneous intestinal perforation (SIP) were significantly better than those in the necrotizing enterocolitis (NEC) group (p < 0.05). Conclusions: Gastrointestinal perforation poses a significant threat the survival of extremely low birth weight (ELBW) infants, with hsPDA and sepsis serving as predisposing factors for gastrointestinal perforation. The gastrointestinal perforation caused by various diseases exhibits distinct clinical characteristics, necessitating tailored surgical approaches based on operative conditions.